Teaching and Research: A Study of Symbiotic Relationship - Rizwan Zaidi; Rohan Kumar; Waseem Fatima (International Journal of Asian Education, 2022)
The present study was conducted to understand the relationship between Researcher-like disposition and teaching effectiveness of teacher educators in two phases. The first Phase was the quantitative Phase, in which Pearson product-moment correlation was carried out to understand the relationship between the variables. One hundred teacher educators are teaching B.Ed. A stratified sampling technique selected the course. The second Phase was the qualitative Phase, in which only 20 teacher educators were randomly selected and interviewed to understand the problems faced by teacher educators in teaching & conducting research. The present study's findings revealed a significant and positive relationship between researcher-like disposition and teaching effectiveness of teacher educators, and the researcher-like disposition has positively contributed to enhancing the teaching effectiveness of teacher educators (p<0.01 level). However, the findings also revealed that the teaching workload, inadequate research pre-service training, infrastructure constraints, Lack of training in ICT, and involvement in other administrative work were the various factors affecting teaching effectiveness and research performance. In a rapidly changing teaching and learning scenario, conducting research is one of the most potential approaches and thoughtful ways to inspire, motivate, and equip teacher educators with skills to teach evidence-based methods. The result of the present study provides a clear picture to the educationists and policymakers to improve the teaching effectiveness and research performance of teacher educators teaching in B.Ed. Institutions.